EFFECTIVENESS OF DISPUTE TECHNIQUE GROUP COUNSELING COGNITIVE IN OVERCOMING FEAR OF FAILURE IN STUDENTS QUR'AN MEMORIZER AT MA TAHFIZHIL QURAN MEDAN - Ayu Muthma'innah Polem; Irwan S (SOSIOEDUKASI, 2025)
The purpose of this study is to ascertain whether group therapy using the Cognitive Dispute approach can help students at MA Tahfizhil Qur'an Medan who memorize the Qur'an overcome the fear of failure. This study uses a quantitative methodology using a Nonequivalent Control Group Design and a Quasi Experimental form. There were 50 students in the study population, 25 of whom were in class XI-A and 25 of whom were in class XI-B. Five students from class XI-A served as the experimental group and five students from class XI-B served as the control group in this study. Purposive sampling is a method used for sampling. With the use of SPSS 22 for WindWos, the data analysis method uses the Mann-Whitney and Wilcoxon tests. Asymp values were obtained using the findings of the Mann-Whitney test. The Wilcoxon test findings showed a result of 0.042 ˂ 0.05, and sig. (2-tailed) is 0.009 ˂ 0.05. According to the test results, there was a striking difference between the experimental and control groups, and it can be concluded that offering group counseling services using the Cognitive Dispute technique helped students who memorized the Qur'an overcome their Fear of Failure.